Functional Coordination of the Chromatin-Remodeling Factor AtINO80 and the Histone Chaperones NRP1/2 in Inflorescence Meristem and Root Apical Meristem - Kang, Huijia; Ma, Jing; Wu, Di; Shen, Wen-Hui; Zhu, Yan (Frontiers in Plant Science, 2019)
Chromatin structure requires proper modulation in face of transcriptional reprogramming in the context of organism growth and development. Chromatin-remodeling factors and histone chaperones are considered to intrinsically possess abilities to remodel chromatin structure in single or in combination. Our previous study revealed the functional synergy between the Arabidopsis chromatin-remodeling factor INOSITOL AUXOTROPHY 80 (AtINO80) and the histone chaperone NAP1-RELATED PROTEIN 1 (NRP1) and NRP2 in somatic homologous recombination, one crucial pathway involved in repairing DNA double strand breaks. Here, we report genetic interplay between AtINO80 and NRP1/2 in regulating inflorescence meristem (IM) and root apical meristem (RAM) activities. The triple mutant atino80-5 m56-1 depleting of both AtINO80 (atino80-5) and NRP1/2 (m56-1) showed abnormal positioning pattern of floral primordia and enlargement of IM size. Several genes involved in auxin pathway (e.g. PIN1, FIL) were found transcriptionally up-regulated in the inflorescences of the triple mutant but barely in those of the single mutant atino80-5 or the double mutant m56-1. In particular, the depletion of AtINO80 and NRP1/2 decreased histone H3 levels within the chromatin regions of PIN1, which encodes an important auxin efflux carrier. Moreover, the triple mutant displayed a severe short-root phenotype with higher sensitivity to auxin transport inhibitor NPA. Unusual high level of cell death was also found in triple mutant root tips, accompanied by DSB damages revealed by -H2A.X loci and cortex cell enlargement. Collectively, our study provides novel insight into the functional coordination of the two epigenetic factors AtINO80 and NRP1/2 in apical meristems during plant growth and development.